ANALISIS KINERJA KEUANGAN DAERAH DAN TINGKATKEMANDIRIAN DAERAH DI KABUPATEN MAGETAN(TAHUN ANGGARAN 2009-2013) - FAMBAYUN, SONIA (Jurnal Akuntansi AKUNESA, 2015)
This purpose of research was to determine the performance of financialmanagement and the degree of independence of Magetan regency area. Analyzerused to measure the performance of the financial management of local and thedegree of independence of Magetan regency area is the ratio of financialindependence area, effectiveness ratio, efficiency ratio, the ratio of the activityand growth ratio. The result of the analysis of the financial performance and thedegree of independence of Magetan regency area in 2009-2013 showed that theratio of financial independence area are instructive with an average of 6,84%,120,62% effectiveness ratio which means it is very effective, the efficiency ratio isefficient with average amounted to 2,40%, the ratio of activity routine expenditureagainst APBD is 62,89% greater than the ratio of activity of developmentexpenditure against APBD that only has an average of 26,08% and the growthratio consist of PAD 17,88%, revenue amounted to 13,35%, 13,92% of routineexpenditure and development expenditure amounted to 14,67%. Keywords: financial performance, APBD, ratio analysis